THE INFLUENCE OF LEADERSHIP STYLE AND WORK MOTIVATION TOWARD EMPLOYEE PERFORMANCE AT DEPARTMENT OF COMMUNICATION AND INFORMATION IN BANDAR LAMPUNG CITY - Tri Lestira Putri Warganegara (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Effortstoimproveemployee performance of Public Work Department of Lampung Province, implementedin the context ofhuman resource management, inorder to realize agood employee, as well as thequalityand vibrantin theline of duty. Employee performanceis influencedbyvariousfactors includingleadership styleandwork motivation. This research is quantitative, descriptive method verification, with a sample of 76 employees at Communications and Information Agency of Bandar Lampung. Collecting data by questionnaires, analysis of data using multiple linear regression model. The results showed: (1) leadership style have a significant effect on employee performance, the coefficient value of 0812 is if the leadership style enhanced the performance of employees will increase. (2) Motivation significant effect on employee performance, the coefficient value of 0786 is if the job motivation improved the performance of employees has increased. (3) The style of leadership and motivation have a significant effect on employee performance with a value of 65.9% ie when the enhanced leadership style and work motivation improved the performance of employees increased better.